Maternal and protective antibody responses to E2 subunit and C-strain classical swine fever vaccines in piglets: a comparative analysis - Ma, Hongwei; Xu, Mengen; Yang, Jie; Zhang, Xiaohu; Liu, Bo; Li, Zuohua; Liu, Zhen; Hu, Wei; Fan, Wei; Li, Jiakui (Frontiers in Veterinary Science, 2025)
Classical swine fever (CSF), caused by the classical swine fever virus (CSFV), is an acute and highly contagious disease affecting swine. In clinical settings, the C- strain vaccine and the E2 subunit vaccine are commonly employed for the prevention and management of the condition. This study monitored the antibody levels of pigs immunized with different CSF vaccines under field conditions, comparing the effects of the classical swine fever virus E2 subunit vaccine and the C-strain vaccine on the duration of maternal antibody maintenance and protective efficacy in fattening pig herds. In the case of sows vaccinated with the E2 subunit vaccine, effective maternal antibodies can be maintained for up to 75 days postpartum, thereby allowing the first vaccination of their piglets to be delayed until 75 days of age. With regard to the immunization of fattening pigs, the E2 subunit vaccine has been demonstrated to confer protection for a period of time sufficient to allow the animals to reach market weight following a single administration of the vaccine. The findings demonstrate that, in comparison with the C-strain vaccine, the E2 subunit vaccine has the capacity to sustain maternal antibodies and protective antibodies over a more protracted period without the necessity for booster immunizations. This translates to a reduction in vaccination frequency and dosage requirements in commercial production. This study provides a theoretical foundation for the optimization of immunization processes within clinical practice.